Utilizamos cookies para personalizar el contenido y la publicidad y para analizar el acceso a nuestro sitio web. Además, nuestros socios para la publicidad online reciben información pseudónima sobre su uso de nuestra página web. políticas sobre cookies y Políticas de privacidad.
 

CPhill

avatar
Nombre de usuarioCPhill
Puntuación103122
Stats
Preguntas 51
Respuestas 31896

 #2
avatar+103122 
+1

 

Here's the answer for anyone who is curious......

 

Join AI,  BI , CI  and DI

 

The semi-perimeter, S, of triangle ABC  =  [ 13 + 14 + 15] / 2  =  42/2   = 21

 

Using Heron's formula to find the the area, we have that the area of ABC

 

A  =√ [ S (S-13) (S-14) (S - 15)  ]   =  √ [21 * 8 * 7 * 6 ]  =  √ [ 3*7 * 8 * 7 * 3 * 2]  =

 

7*3√ [  8 *2]  =     21√16  =  21 * 4  = 84

 

Now  we have triangles ABI ,   BCI  and  CAI   with altitudes  FI, DI and EI , respectively

 

And each of these altitudes = the radius of the in-circle  

 

So    the area of ABC  =  S * radius...so we have

 

84 =  21 * radius

 

84 / 21  =  radius  =  4  = altitude of  ABI, BCI  and CAI

 

Let   BD, BF  = x     CD, CE  = y  and   AF, AE  = z

 

So.....  BD + CD  = 14     so  x + y  =14     (1)

And BF + AF = 13       so  x + z = 13   ⇒  -x - z = -13       (2)

And  CE  + AE  = 15    so   y + z = 15        (3)  

 

Add (2) and (3)  and we have that  y - x = 2    add this result  to (1)  and we have that

 

2y  = 16

y = 8  

So  z = 7    and x = 6

 

So  the area of  AEIF  =  area of triangle AFI  + area of triangle AEI

 

But  triangles AFI  and AEI  are  congruent right triangles....so we can call the area of AEIF  =  2 area of triangle AFI

 

area of triangle AFI =  (1/2) ( radius) (  AF)  =  (1/2) (4) ( z)  = (1/2)(4)(7)  =  14

 

So

 

2* area of triangle AFI  =  2 * 14 =  28  = area of AEIF 

 

 

 

cool cool cool

23 ago. 2019
 #1
avatar+103122 
+2

                 x^15   + x^13  + x^11  + x^10  + x^9   + x^8 + x^7 +x^6  + x^5 + 2x^4 + x^3  + 2x^2 + 2x + 2

x^3  - x  [  x^18     +      x^13      +    x^7    +     x^4  ]

                x^18  - x^16

              ___________________________________

                          x^16   +   x^13    +  x^7   +     x^4

                          x^16  - x^14

                         ____________________________

                               x^14  + x^13 + x^7 + x ^4

                               x^14   -x^12

                             ______________________

                                     x^13 + x^12 + x^7 + x^4

                                     x^13 - x^11

                                 ______________________

                                       x^12 + x^11 + x^7  + x^4

                                       x^12 - x^10

                                       ____________________

                                        x^11 + x^10 + x^7 + x^4

                                        x^11 - x^9 

                                      _____________________

                                        x^10 + x^9 + x ^7 + x^4

                                        x^10  - x^8

                                      ______________________

                                         x^9  + x^8  + x^7  + x^4

                                         x^9            -x^7

                                       _____________________

                                              x^8  + 2x^7  + x^4

                                              x^8   -x^6

                                             ________________

                                               2x^7  + x^6 + x^4

                                               2x^7 - 2x^5

                                              ________________

                                               x^6  + 2x^5  + x^4

                                               x^6                -x^4

                                             _________________

                                                       2x^5 + 2x^4

                                                       2x^5  - 2x^3

                                                     _____________

                                                         2x^4  + 2x^3

                                                         2x^4  - 2x^2

                                                        ___________

                                                          2x^3  + 2x^2

                                                          2x^3  - 2x

                                                        ____________

                                                         2x^2  + 2x   =  the remainder

 

 

 

cool cool cool   

23 ago. 2019